PSYCHOLOGY OF MUSİCAL ABİLİTİES - Rasulova Saida Sabirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article talks about the inner experiences of the future composer, performer, musicologist, educator, his thoughts and aspirations, the flight of analytical calculations and visions, work on a musical work and its performance in a concert, will and memory, character and abilities, as well as the fact that the musician and listener can well know and adequately accurately imagine other psychological qualities of his personality.